ΔΗΜΗΤΡΗΣ ΧΕΙΛΑΡΗΣ, Μεταπλάσεις του μύθου της Πηνελόπης στη νεοελληνική μεταπολεμική ποίηση - Χείλαρης Δημήτρης (Σύγκριση/Comparaison/Comparison, 2022)
Transformations of the myth of Penelope in modern Greek post-war poetry The research of the mythical texts, i.e. the multiple versions and representations of the myth in the Modern Greek literature, constitutes one of the most interesting fields of research of both modern Greek and Comparative Literature. The interpretive study of the myth in the post-war generations and the investigation of its transformations during this period is still an open issue of Humanities. The mythological character of Penelope consists of a heroine, which has faced various transformations, both in modern Greek and western traditions, confirming the multiform core of the myth. This paper aims to focus on the thematic transformations of myth in modern Greek post-war poetry using the tools of the theory of literature and comparative philology. Admittedly, during the 19th and 20th centuries, the image of the faithful wife is dominant. However, in late rewritings, this image is generally changed; from the self-referential Penelope of Katerina Aggelaki-Rouk, the ironic Penelope of Vavouris to the contemporary Penelope of Manos Eleftheriou, this heroine is constantly transformed. Besides, it’s a commonplace that the historical and socio-political reality of that morally and ideologically crucial era played a decisive role for the multiple transformations of the myths and for determining the position of the female sex, which also justifies the different mythological reinterpretations. The myth either underlines the painful historical conditions or triggers the creation of a personal mythology. Finally, myth appears as a channel for returning to the ancient Greek cultural heritage or constitutes a personal testimony to the existential pain of the modern individual.